Comparative Endothelialization of the Watchman Plug Device and LACBES Pacifier Occluder after Left Atrial Appendage Closure - Jing Zhou; Zongqi Zhang; Kandi Zhang; Tiantian Zhang; Qing He; Junfeng Zhang (Reviews in Cardiovascular Medicine)
Background: For patients with nonvalvular atrial fibrillation (NVAF), left atrial appendage closure (LAAC) is an alternative to oral anticoagulants (OACs). However, incomplete device endothelialization (IDE) after LAAC has been linked to device-related thrombus (DRT) and subsequent thromboembolic events. Here, the differences in device endothelialization between the Watchman plug device and the LACBES pacifier occluder after implantation were investigated. Methods: Of 201 consecutive patients with indications for LAAC, 101 received a Watchman 2.5 device, and 100 received a LACBES occluder. IDE was defined as a residual flow of contrast agent inside the left atrial appendage (LAA) on cardiac computed tomography angiography (CCTA) without peri-device leak (PDL) at the 3-month and 6-month follow-ups. Results: There were no significant differences in DRT or PDL incidence between the two groups. However, the IDE rate in the absence of PDL was higher in the LACBES group than in the Watchman group at 3 months (42.4% versus 25.8%; p = 0.025) and at the 6-month follow-up (24.7% versus 11.2%; p = 0.028) as determined by CCTA. Conclusions: Our findings indicated that the LACBES occluder took longer to complete endothelialization than the Watchman device after successful LAAC therapy. CCTA is a reliable imaging method for assessing the sealing of LAAC devices and confirming complete device endothelialization.